Application of sodium alginate and preparation method of lithium ion battery electrode plate
By using sodium alginate as an aqueous adhesive and combining a mixed solvent of ethanol and water, lithium-ion battery electrode sheet was prepared, which solved the problem that PVDF adhesive was not suitable in the field of silicon-based negative electrodes in the prior art, and achieved uniformity, stability and environmental protection of the electrode sheet.
Patent Information
- Application Number
- CN202411886430.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-19
AI Technical Summary
In the existing lithium-ion battery electrode production process, the PVDF adhesive used is not suitable for some materials, especially in the field of silicon-based negative electrodes, which cannot effectively release the stress caused by the volume expansion effect during charging and discharging, resulting in attenuation or failure of material properties. At the same time, PVDF has the disadvantages of high toxicity, poor safety and environmental protection.
Sodium alginate is used as an aqueous adhesive, combined with a mixed solvent of ethanol and water, and a slurry is formed by grinding the electrode active material, conductive additives and sodium alginate powder, and coated on copper foil. After step-by-step drying and rolling treatment, a lithium-ion battery electrode sheet is prepared.
This method provides an electrode sheet preparation process with excellent safety performance and obvious cost advantages. The prepared electrode sheet is uniform and does not crack, showing excellent cycle stability, and the process is simple to operate and low cost, and has the characteristics of green and environmental protection.
Smart Images

Figure CN119674081A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to an application of sodium alginate and a method for preparing a lithium ion battery electrode sheet. Background Art
[0002] In recent years, environmental and energy issues have become increasingly severe. The development of electrochemical large-scale energy storage is an effective way to alleviate the uneven distribution of energy in time and space. Lithium-ion batteries have always been considered an efficient and convenient energy storage device, and electrode materials, as an important component of batteries, are usually composed of active substances and conductive current collectors. Conductive agents and adhesives are added to the active materials to bond with the electrode conductive layer, and finally dried and rolled to form battery electrodes.
[0003] At present, the electrode production process disclosed in China generally uses PVDF as a binder, which requires the use of oily solvents such as N-methylpyrrolidone as diluents when preparing the active material slurry. However, due to its low Young's modulus, the bonding performance of PVDF material is far from meeting the requirements of electrode materials. In addition, when the negative electrode uses materials such as silicon oxide, PVDF cannot effectively release the stress generated by the volume expansion effect during the charge and discharge process, which can easily cause the material performance to decay or even fail. In addition, organic binders have the disadvantages of high toxicity and poor safety and environmental protection.
[0004] Therefore, selecting a suitable adhesive to replace PVDF and developing a set of related electrode sheet preparation processes are issues that need to be urgently addressed. Summary of the invention
[0005] In view of this, the present application provides an application of sodium alginate and a method for preparing a lithium-ion battery electrode sheet, aiming to improve the problem that the current PVDF adhesive is not applicable to certain materials, especially silicon-based negative electrodes.
[0006] To achieve the above object, the present invention discloses the use of sodium alginate as an aqueous adhesive in the preparation of lithium ion battery electrode sheets.
[0007] The present invention also discloses a method for preparing a lithium ion battery electrode sheet, comprising the following steps:
[0008] Step 1: fully mix the electrode active material, the conductive additive and the adhesive, and grind them into powder;
[0009] Step 2, adding a mixed solvent of water and ethanol to the powder in step 1, grinding it fully into slurry and then coating it on the copper foil;
[0010] Step 3, drying the copper foil after step 2 in a stepwise manner, rolling it, and cutting it into small discs to obtain a lithium-ion battery electrode sheet;
[0011] Wherein, the adhesive is sodium alginate.
[0012] In a preferred embodiment of the present invention, in step 1, the electrode active material is a silicon-carbon negative electrode material with a diameter of 100 nm, and the conductive additive is conductive carbon black.
[0013] In a preferred embodiment of the present invention, in step 1, the mass ratio of the electrode active material, the conductive additive and the binder is 3:1:1.
[0014] In a preferred embodiment of the present invention, in step 2, the volume ratio of water to ethanol in the mixed solvent is 7:1, and the mass volume ratio of the powder to the mixed solvent is 100:1.6 (mg / mL).
[0015] In a preferred embodiment of the present invention, in step 2, the copper foil has a thickness of 10 μm, and the thickness of the slurry coated on the copper foil has a thickness of 25 μm.
[0016] In a preferred embodiment of the present invention, in step 2, before coating the slurry on the copper foil, it also includes the step of modifying the surface of the copper foil: dripping a wetting agent on the surface of the copper foil, removing the surface air, and modifying the surface to facilitate the scraping and covering of the electrode material.
[0017] Preferably, the wetting agent is ethanol.
[0018] In a preferred embodiment of the present invention, in step 3, the step-by-step drying method is: heating from room temperature to 60°C, with a heating rate of 10°C / min, and drying for 4 hours at normal pressure; then transferring to a vacuum drying oven, heating to 105°C at a heating rate of 5°C / min, keeping warm for 24 hours, and then cooling to room temperature at a rate of 10°C / min.
[0019] In a preferred embodiment of the present invention, in step 3, the force applied during rolling is 100N.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention selects sodium alginate, an aqueous adhesive with a high Young's modulus, and provides a complete electrode sheet preparation process matched therewith, and the method has good safety performance and cost advantages. The electrode sheet prepared by the method is uniform, does not crack, and exhibits excellent cycle stability. The process is simple to operate, low in cost, and highly repeatable between batches. Ethanol and water are used as mixed solvents, and it is green, safe and environmentally friendly, and is an environmentally friendly technology.
[0022] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a scanning electron microscope (SEM) image of a cross section of a battery electrode sheet prepared in Example 1 of the present invention;
[0024] Figure 2 This is a scanning electron microscope (SEM) image of the surface of the electrode sheet prepared in Example 1;
[0025] Figure 3 This is an optical photograph of the electrode sheet scraped in Example 1;
[0026] Figure 4 This is an optical photograph of the electrode sheet scraped by Comparative Example 2;
[0027] Figure 5 This is an optical photograph of the electrode sheet after drying in Example 1;
[0028] Figure 6 This is an optical photograph of the electrode sheet after drying in Comparative Example 3;
[0029] Figure 7 This is an optical photograph of the electrode sheet scraped by Comparative Example 4;
[0030] Figure 8 This is a test chart of the cycle stability performance of the half-cell assembled in comparative example 5.
[0031] Fig. 9 This is a test chart of the cycle stability performance of the half-cell assembled for Comparative Example 6. DETAILED DESCRIPTION
[0032] The following describes several preferred embodiments of the present invention with reference to the drawings in the specification, so that the technical content is clearer and easier to understand. The present invention can be embodied in many different forms of embodiments, and the protection scope of the present invention is not limited to the embodiments mentioned in the text.
[0033] In the drawings, components with the same structure are indicated by the same numerical reference numerals, and components with similar structures or functions are indicated by similar numerical reference numerals. The size and thickness of each component shown in the drawings are arbitrarily shown, and the present invention does not limit the size and thickness of each component. In order to make the illustration clearer, the thickness of the components is appropriately exaggerated in some places in the drawings.
[0034] Embodiment 1:
[0035] (1) Mix 30 mg of silicon-carbon anode material (diameter about 100 nm), 10 mg of conductive carbon black and 10 mg of sodium alginate, and grind the powder in a mortar for 1 h;
[0036] (2) adding 0.8 mL of a mixed solvent of water and ethanol (volume ratio 7:1) to the powder of step (1) and grinding thoroughly for 30 min to form a slurry;
[0037] (3) A certain amount of ethanol is first dripped onto the rough side of the 10 μm thick copper foil to wet it. The purpose is to remove the air on the surface and slightly modify the surface so that the electrode material can be better coated.
[0038] (4) Scrape the slurry from step (2) onto the surface of the copper foil with a scraping thickness of 25 μm. After scraping, place it on the table for 30 minutes;
[0039] (5) Transfer the electrode of step (4) to an oven, heat it from room temperature to 60°C at a heating rate of 10°C / min, and dry it for 4 h at normal pressure; then transfer it to a vacuum drying oven, heat it to 105°C at a heating rate of 5°C / min, keep it at that temperature for 24 h, then cool it to room temperature at a rate of 10°C / min and take it out.
[0040] (6) The electrode sheets are rolled out with a force of 100 N. After rolling, they are cut into small discs and assembled into batteries.
[0041] Comparative Example 1
[0042] (1) Mix 30 mg of silicon-carbon anode material (diameter about 100 nm), 10 mg of conductive carbon black and 10 mg of sodium alginate, and grind the powder in a mortar for 1 h;
[0043] (2) adding 0.8 mL of water to the powder obtained in step (1) and grinding the powder for 30 min to form a slurry;
[0044] (3) Scrape the slurry from step (2) onto the rough side of a 10 μm copper foil with a scraping thickness of 25 μm. After scraping, place the slurry on the table for 30 minutes;
[0045] (4) Transfer the electrode of step (3) to an oven, heat it from room temperature to 60°C at a heating rate of 10°C / min, and dry it for 4 h at normal pressure; then transfer it to a vacuum drying oven, heat it to 105°C at a heating rate of 5°C / min, keep it at that temperature for 24 h, then cool it to room temperature at a rate of 10°C / min and take it out.
[0046] (5) The electrode sheets are rolled and pressed with a force of 100 N. After rolling, they are cut into small discs and assembled into batteries.
[0047] Comparative Example 2
[0048] (1) Mix 30 mg of silicon-carbon anode material (diameter about 100 nm), 10 mg of conductive carbon black and 10 mg of sodium alginate, and grind the powder in a mortar for 1 h;
[0049] (2) adding 0.8 mL of a mixed solvent of water and ethanol (volume ratio 7:1) to the powder of step (1) and grinding thoroughly for 30 min to form a slurry;
[0050] (3) A certain amount of ethanol is first dripped onto the rough side of the 10 μm thick copper foil to wet it. The purpose is to remove the air on the surface and slightly modify the surface so that the electrode material can be better coated.
[0051] (4) Scrape the slurry from step (2) onto the surface of the copper foil with a scraping thickness of 25 μm. After scraping, place it on the table for 30 minutes;
[0052] (5) Transfer the electrode obtained in step (4) to a vacuum drying oven, heat the temperature to 105°C at a rate of 5°C / min, keep the temperature for 24 h, then cool the temperature to room temperature at a rate of 10°C / min and take the electrode out.
[0053] (6) The electrode sheets are rolled out with a force of 100 N. After rolling, they are cut into small discs and assembled into batteries.
[0054] Comparative Example 3
[0055] (1) Mix 30 mg of silicon-carbon negative electrode material (diameter about 100 nm), 10 mg of conductive carbon black and 10 mg of sodium alginate;
[0056] (2) adding 0.8 mL of a mixed solvent of water and ethanol (volume ratio 7:1) to the powder of step (1) and grinding thoroughly for 30 min to form a slurry;
[0057] (3) A certain amount of ethanol is first dripped onto the rough side of the 10 μm thick copper foil to wet it. The purpose is to remove the air on the surface and slightly modify the surface so that the electrode material can be better coated.
[0058] (4) Scrape the slurry from step (2) onto the surface of the copper foil with a scraping thickness of 25 μm. After scraping, place it on the table for 30 minutes;
[0059] (5) Transfer the electrode obtained in step (4) to a vacuum drying oven, heat the temperature to 105°C at a rate of 5°C / min, keep the temperature for 24 h, then cool the temperature to room temperature at a rate of 10°C / min and take the electrode out.
[0060] (6) The electrode sheets are rolled out with a force of 100 N. After rolling, they are cut into small discs and assembled into batteries.
[0061] Comparative Example 4
[0062] (1) Mix 30 mg of pure silicon material (about 50 nm in diameter), 10 mg of conductive carbon black and 10 mg of sodium alginate, and grind the powder in a mortar for 1 h;
[0063] (2) adding 0.8 mL of a mixed solvent of water and ethanol (volume ratio 7:1) to the powder of step (1) and grinding thoroughly for 30 min to form a slurry;
[0064] (3) A certain amount of ethanol is first dripped onto the rough side of the 10 μm thick copper foil to wet it. The purpose is to remove the air on the surface and slightly modify the surface so that the electrode material can be better coated.
[0065] (4) Scrape the slurry from step (2) onto the surface of the copper foil with a scraping thickness of 25 μm. After scraping, place it on the table for 30 minutes;
[0066] (5) Transferring the electrode of step (4) to an oven, heating the temperature from room temperature to 60°C at a heating rate of 10°C / min, and drying for 4 h at normal pressure; then transferring to a vacuum drying oven, heating the temperature to 105°C at a heating rate of 5°C / min, keeping the temperature for 24 h, then cooling the temperature to room temperature at a rate of 10°C / min, and taking out;
[0067] (6) The electrode sheets are rolled out with a force of 100 N. After rolling, they are cut into small discs and assembled into batteries, and the performance of the half-cells is tested.
[0068] Comparative Example 5
[0069] (1) Mix 30 mg of pure silicon material (about 50 nm in diameter), 10 mg of conductive carbon black and 10 mg of PVDF, and grind the powder in a mortar for 1 h;
[0070] (2) adding 0.8 mL of N-methylpyrrolidone to the powder obtained in step (1) and grinding the powder for 30 min to form a slurry;
[0071] (3) Scrape the slurry from step (2) onto the rough side of a 10 μm thick copper foil to a thickness of 25 μm. After the scraping is completed, place it on the table for 30 minutes;
[0072] (4) Transfer the electrode of step (3) to an oven, heat it from room temperature to 60°C at a heating rate of 10°C / min, and dry it for 4 h at normal pressure; then transfer it to a vacuum drying oven, heat it to 105°C at a heating rate of 5°C / min, keep it at that temperature for 24 h, then cool it to room temperature at a rate of 10°C / min and take it out.
[0073] (5) The electrode sheets were rolled and pressed with a force of 100 N. After rolling, they were cut into small discs and assembled into batteries. The battery performance was tested and the cycle current density was 0.1 A / g.
[0074] The above is a detailed introduction to the method for preparing lithium-ion battery electrode sheets using a water-based adhesive in the present application. Specific examples are used in this article to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.
Claims
1. Application of sodium alginate as a water-based adhesive in the preparation of lithium-ion battery electrode sheets.
2. A method for preparing a lithium ion battery electrode sheet, characterized in that: The steps include: Step 1: fully mix the electrode active material, the conductive additive and the adhesive, and grind them into powder; Step 2, adding a mixed solvent of water and ethanol to the powder in step 1, grinding it fully into slurry and then coating it on the copper foil; Step 3, drying the copper foil after step 2 in a stepwise manner, rolling it, and cutting it into small discs to obtain a lithium-ion battery electrode sheet; Wherein, the adhesive is sodium alginate.
3. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 1, the electrode active material is a silicon-carbon negative electrode material with a diameter of 100 nm, and the conductive additive is conductive carbon black.
4. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 1, the mass ratio of the electrode active material, the conductive additive and the adhesive is 3:1:
1.
5. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 2, the volume ratio of water to ethanol in the mixed solvent is 7:1, and the mass volume ratio of the powder to the mixed solvent is 100:1.6 (mg / mL).
6. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 2, the copper foil has a thickness of 10 μm, and the thickness of the slurry coated on the copper foil is 25 μm.
7. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 2, before coating the slurry on the copper foil, the step of modifying the surface of the copper foil is also included: dripping a wetting agent on the surface of the copper foil, removing the surface air, and modifying the surface to facilitate the scraping and covering of the electrode material.
8. The method for preparing a lithium ion battery electrode sheet according to claim 7, characterized in that: The wetting agent is ethanol.
9. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 3, the step drying method is: heating from room temperature to 60°C, with a heating rate of 10°C / min, and drying for 4 hours at normal pressure; then transferring to a vacuum drying oven, heating to 105°C at a heating rate of 5°C / min, keeping warm for 24 hours, and then cooling to room temperature at a rate of 10°C / min.
10. The method for preparing a lithium ion battery electrode sheet according to claim 2, characterized in that: In step 3, the force applied during rolling is 100N.
Citation Information
Patent Citations
Application of alginate as a binder in electrode preparation
CN102280642A
Method for preparing Si / C composite cathode material of lithium ion battery
CN103078092A
Preparation method of silicon-based negative pole piece of high-performance lithium ion battery
CN114335438A